A Critical Discourse Analysis towards Utterances in Dentist-Patient Communication - Novia Ardishanti; Muhammad Yudhist Alfiananda Rusnanto (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
The interaction between dentists and patients has been a common issue. Nevertheless, the study regarding the Critical Discourse Analysis on utterances used by dentists when taking care of patients remains unknown. This study aims to discover (1) the experience of fresh-graduate dentists in learning how to interact or communicate with patients at their undergraduate program (past experience) and (2) how they use utterances in taking care of patient (current experience). In achieving the goals of the study, researchers employed narrative inquiry as the design of this study and used open-ended questions as a means of collecting data. The collected data was then analyzed in regard to the Critical Discourse Analysis to find whether the utterances used in taking care of patients were relevant to the knowledge they obtained in undergraduate program. Outcome of this study reveals that the experience regarding communication between dentists and patients, both in undergraduate program and at current practice, are interconnected to each other.